2016
DOI: 10.5935/0101-2800.20160054
|View full text |Cite
|
Sign up to set email alerts
|

Screening for BK virus nephropathy in kidney transplant recipients: comparison of diagnostic tests

Abstract: Urine cytology and qPCR in blood and urine are commonly used to screen renal transplant recipients for polyomavirus-associated nephropathy (PVAN). Few studies, however, have directly compared these two diagnostic tests, in terms of their performance to predict PVAN. This was a systematic review in which adult (≥ 18 years old) renal transplant recipients were studied. A structured Pubmed search was used to identify studies comparing urine cytology and/or qPCR in urine and plasma samples for detecting PVAN with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 0 publications
1
8
0
1
Order By: Relevance
“…The study was retrospective and single center and these results should therefore be confirmed at other centers using different immunosuppression and other clinical protocols. The majority of BKPyVAN cases were presumptively diagnosed based on viral load threshold rather than by biopsy, but a well‐validated virologic threshold was used for diagnosis, and the characteristics and outcomes of those with presumptive and proven BKPyVAN were similar (Table ). The inclusion of both presumptive and biopsy‐proven cases allowed an analysis reflective of the full clinical spectrum of BKPyVAN and avoided inappropriate misclassification of cases with false negative biopsies .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study was retrospective and single center and these results should therefore be confirmed at other centers using different immunosuppression and other clinical protocols. The majority of BKPyVAN cases were presumptively diagnosed based on viral load threshold rather than by biopsy, but a well‐validated virologic threshold was used for diagnosis, and the characteristics and outcomes of those with presumptive and proven BKPyVAN were similar (Table ). The inclusion of both presumptive and biopsy‐proven cases allowed an analysis reflective of the full clinical spectrum of BKPyVAN and avoided inappropriate misclassification of cases with false negative biopsies .…”
Section: Discussionmentioning
confidence: 99%
“…Biopsy‐proven BKPyVAN was diagnosed by renal allograft biopsy that demonstrated typical viral inclusions that were positive for SV40 antigen as described previously . Presumptive BKPyVAN was defined as a plasma BKPyV load >10 000 BKPyV DNA copies/mL, a well‐validated, sensitive, and specific threshold for biopsy‐proven BKPyVAN, as previously described . Proven and presumed cases were pooled for analysis to reflect the entire spectrum of clinical BKPyVAN, to include true cases of BKPyVAN that might have been missed because of a falsely negative biopsy, and because these clinical entities have been shown to have a generally similar histologic and clinical course .…”
Section: Methodsmentioning
confidence: 99%
“…1,2 NAT in urine, in the absence of an elevated BKPyV plasma load is not associated with an increased risk for BKPyVAN. Pinto et al 7 concluded that positive BKPyV in two or more urine samples was helpful to predict BKPyV viremia with 100% sensitivity, 94% specificity and a PPV of 50% and NPV of 100%. Plasma NAT has the best PPV for BKPyVAN and has been used for most transplant centers for BKPyV screening; the sensitivity to predict BKPyVAN was 60-100%, specificity was 33-100%, and PPV was 72-100%.…”
Section: Analysis Of Diagnostic Methods As a Screening Test To Detectmentioning
confidence: 99%
“…As reported by Pinto et al, the different techniques limit the comparison between quantitative NATs and there is a need for standardization for BKPyV-related tests. 7 PCRs with primers and probes targeting the variable regions of the genome, like the NCCR or VP1 regions, may give false negative results or incorrect viral loads when samples contain rare genotypes. 10 In addition, urine "decoy cells" detection presents a considerable pre-analytical logistics and an analytical laboratory expertise; the exam should be performed in fresh urine, and inconclusive results are frequent during the first months post-transplant due the high urinary sediment.…”
Section: Analysis Of Diagnostic Methods As a Screening Test To Detectmentioning
confidence: 99%
See 1 more Smart Citation